My tang's tungled and other ridiculous situations - Brewton, Sara Westbrook; Brewton, John Edmund 1898-; Blackburn, G. Meredith; Booth, Graham (New York Crowell, 1973)
A collection of humorous and nonsense poems by well-known writers.
Keywords: Children's poetry; Humorous poetry; Limericks